2022
DOI: 10.1111/jfpp.16353
|View full text |Cite
|
Sign up to set email alerts
|

Annealing treatment of ulluco starch: Effect of moisture content and time on the physicochemical properties

Abstract: Annealing is a modification method that can improve the physicochemical properties of starch. The effect of moisture content (MC) and time (t) on the physicochemical properties of ulluco starch obtained by annealing (ANN) modification was studied.The results showed the ulluco-modified starches improved physicochemical properties such as solubility, water-holding capacity (WHC), oil-holding capacity (OHC), pasting properties, and the texture of the gel formed. Furthermore, the ordered structure and granules sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…All samples exhibited a band at 3300 cm −1 corresponding to the stretching of hydroxyl groups (–O–H) [ 11 ]. A previous report observed that the native ulluco starch and the modified starches presented the same band at 3446 cm −1 [ 7 ]. However, there was a slight shift in the signal in the films analyzed.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…All samples exhibited a band at 3300 cm −1 corresponding to the stretching of hydroxyl groups (–O–H) [ 11 ]. A previous report observed that the native ulluco starch and the modified starches presented the same band at 3446 cm −1 [ 7 ]. However, there was a slight shift in the signal in the films analyzed.…”
Section: Resultsmentioning
confidence: 97%
“…The XRD patterns of biodegradable films are presented in Figure 3 . All samples showed a typical B-type crystal structure similar to the native ulluco starch [ 7 ]. This structure showed characteristic peaks at around 5.6° 2θ and 17° 2θ (peak with strong diffraction intensity) and with small peaks at around 15°, 20°, 22°, and 24° 2θ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations